Screening of fertility restorers for cytoplasmic genic male sterile (CGMS) lines in rice (oryza sativa L.). - Adarsha B (Department of Plant Breeding and Genetics, College of Horticulture, 2011)
The study entitled “Screening of fertility restorers for Cytoplasmic Genic Male Sterile (CGMS) lines in Rice (Oryza sativa L.)” was conducted in the Department of Plant Breeding and Genetics, College of Horticulture during the period 2009-11. The study envisaged evaluation of different CGMS sources and identification of potential restorers and maintainers among high yielding varieties of Kerala. Separate experiments viz., 1. Morphological evaluation of parents and 2. Development and evaluation of F1 hybrids, conducted to realize the objectives. Materials for the present study comprised of two CGMS lines viz., CMS 2A from Tamil Nadu Agricultural University, Coimbatore and IR 68897A, from Directorate of Rice Research, Hyderabad. Seven popular high yielding varieties of Kerala were used as male parents. Parental lines were raised and observations on qualitative and quantitative traits were recorded. Hybridization was done between CGMS lines and restorers in Line x Tester design. The F1 and the parents were raised and observations were recorded. The results on qualitative traits showed that the male parents Onam and Uma had well exserted panicle, semi-erect flag leaf orientation and well exserted stigma which are helpful in out crossing. None of the hybrids were found to be superior to parents with respect to yield due to increased spikelet sterility. Even though, hybrids CMS 2A x Kanchana, CMS 2A x Onam, IR 68897A x Aiswarya and IR 68897A x Uma recorded high pollen fertility none of the male lines can be considered as restorer. The varieties Aiswarya, Jyothi, Kanchana, Matta Triveni, Onam and Uma can be considered as a partial restorer for CGMS line CMS 2A. For the CGMS line IR 68897A, the male lines, Aiswarya, Jaya, Jyothi, Matta Triveni and Uma can be considered as partial restorer. Considering the pollen fertility of CGMS line CMS 2A, Jaya with 43.73 per cent pollen fertility can be considered as partial maintainer and for IR 68897A, Kanchana and Onam can be identified as a partial maintainer. However, in the hybrids CMS 2A x Uma and IR 68897A x Onam, few plants exhibited high pollen sterility per cent. These can be utilized to develop CGMS lines in the genetic background of Uma/Onam in future, through backcross breeding programme.